2013
DOI: 10.1016/j.archoralbio.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Imaging analysis of early DMP1 mediated dentine remineralization

Abstract: Objective This study assessed the micro-morphological changes in demineralized dentin scaffold following incubation with recombinant dentin matrix protein 1 (rDMP1). Design Extracted human molar crowns were sectioned into 6 beams (dimensions: 0.50 × 1.70 × 6.0 mm), demineralized and incubated overnight in 3 different media (n = 4): rDMP1 in bovine serum albumin (BSA), BSA and distilled water. Samples were placed in a chamber with simulated physiological concentrations of calcium and phosphate ions at constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Phosphoric acid did not solubilize collagen or GAGs and resulted in minimal detection of PGs (Bedran-Russo et al 2013). Therefore, it is reasonable to suggest that our milder EDTA treatment should not have affected any of these organic components; however, these ECM molecules were not investigated (B) corresponding SAED diffraction pattern for mineral crystal nucleated by pB that displays a diffuse (2 1 1) ring that is characteristic of impure hydroxyapatite (HA); (C) representative mineral crystal nucleated by a 1:4 ratio of pA:pB; (D) SAED diffraction pattern corresponding to mineral nucleated by a 1:4 ratio of peptides, resulting in a (0 0 2) ring as well as several concentric rings, indicating the presence of rod-like HA crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoric acid did not solubilize collagen or GAGs and resulted in minimal detection of PGs (Bedran-Russo et al 2013). Therefore, it is reasonable to suggest that our milder EDTA treatment should not have affected any of these organic components; however, these ECM molecules were not investigated (B) corresponding SAED diffraction pattern for mineral crystal nucleated by pB that displays a diffuse (2 1 1) ring that is characteristic of impure hydroxyapatite (HA); (C) representative mineral crystal nucleated by a 1:4 ratio of pA:pB; (D) SAED diffraction pattern corresponding to mineral nucleated by a 1:4 ratio of peptides, resulting in a (0 0 2) ring as well as several concentric rings, indicating the presence of rod-like HA crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The demineralized dentin wafer tissues (kind gift from Dr. Bedran-Russo, Department of Restorative Density, UIC) were treated with trypsin to remove the noncollagenous proteins as published earlier3435. The wafers were dehydrated in a series of ethanol from 30 to 100%, trimmed, embedded in epoxy resin and ultrathin sections (70 nm) were placed on 300 mesh formvar carbon coated nickel grids.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, our results are in line with other studies that also observed an effect of DMPs on demineralized dentin, supporting the conclusion that DMPs promote the deposition and nucleation of HA. For example, Bedran-Russo et al showed in their study that “DMP1-treated samples promoted deposition of amorphous calcium phosphate (ACP) precursors and needle-shaped hydroxyapatite crystals surrounding collagen fibrils” [22]. Liu et al came to the conclusion that “synthetic peptides derived from DMP1 bind type I collagen and promote nucleation of HA” [23].…”
Section: Discussionmentioning
confidence: 99%